Measuring parental dimensions: A psychometric evaluation of the parents as social context questionnaire, Swedish version - Keijser Rebecka; Nilsson W. Kent; Åslund Cecilia (Cogent Psychology, 2020)
The relationship between a parent and an adolescent is dynamic. A parent may do better in certain areas or during certain phases of the adolescent’s life, and the adolescent’s needs or demands on the parent may vary accordingly. Parental dimensions have been used to evaluate the quality of a parent–child relationship. The present study explored the structure of a translated version of the Parents as Social Context Questionnaire (PASCQ), both a parent and an adolescent version. The participants were 1556 Swedish adolescents 16–18 years (mean age = 17.4 years, 58.3% females), and 1477 parents, including 1345 parent–adolescent dyads. The results of the confirmatory factor analyses provided a significant model fit of the six parental dimensions (Warmth, Rejection, Structure, Chaos, Autonomy support and Coercion) of PASCQ regarding both the parent- and adolescent reports. Therefore, the Swedish version of the PASCQ parent and adolescent reports is suitable for measuring the six parental dimensions of the PASCQ. However, the concordance between the two reports was low, suggesting that the parent report may be suitable for measuring the parent’s view of the relationship, but may be less representative of the adolescent’s experiences and vice versa. These results can contribute to future work on parenting in general and parental dimensions in association with adolescents in particular.